Pleuroperitoneal communication-associated pleuritis as an uncommon cause of fever of unknown origin in a child on peritoneal dialysis: a case report - Juhee Park; Heeyon Yoon; Jiwon Jung; Jina Lee; Joo Hoon Lee (Korean Society of Pediatric Nephrology, 2023)
Pleuroperitoneal communication (PPC) is a rare mechanical complication of peritoneal dialysis (PD), which causes dialysate to move from the peritoneal cavity to the pleural cavity, resulting in pleural effusion. Typically, PPC is discovered through pleural effusion in PD patients who are not in volume overload status. A unique characteristic of the pleural effusion caused by PPC is that it is not resolved by increasing ultrafiltration by dialysis. In this report, we present a 7-year-old girl with PD after birth with the history of various infectious PD-related complications, presenting with fever ongoing for 6 months. PPC-associated pleuritis was suspected as the cause of fever, which eventually developed after long-term PD and induced complicated pleural effusion, lung inflammation, and prolonged fever for 6 months.